Pemetaan Dan Analisis Tingkat Radiasi Gelombang Extremely Low Frequency (Elf) Pada Permukaan Bumi Tertentu Sebagai Suatu Pendekatan Ilmiah Terhadap Fenomena Paranormal (Studi Kasus Pada Tempat-Tempat Angker Di Kabupaten Alor) - Imanuel Christian Mauko; Robinson A Wadu; Nicodemus Mardanus Setiohardjo (Jurnal Ilmiah Flash, 2020)
The existence of Extremely Low Frequency (ELF) waves in several places on earth, also influences the socio-cultural mindset of certain people who strongly believe in paranormal, superstitious and mystical stories about the existence of ghosts around them. One of the places known for its paranormal practice is the people who inhabit Alor Island in Alor Regency, East Nusa Tenggara, Indonesia. This paranormal phenomenon still cannot be explained logically, so that sometimes it causes complicated social problems in society, even the stikma of "Orang Alor Suanggi" appears in social interactions. This research was conducted to find out the existence of Earth's Extremely Low Frequency (ELF) electromagnetic field radiation at a certain location with a case study in Alor Regency. This research was conducted by measuring the level of Extremely Low Frequency (ELF) wave radiation using an EMF detector at haunted / sacred places in Alor Regency and connecting it with paranormal events in the community. The results of the research prove that several locations in Alor Regency have high exposure to ELF wave radiation and the effect of the earth's magnetic field is quite large. The village in Subo Village which has the highest observed ELF wave radiation with value at 815 V / M, while the highest instantaneous ELF wave radiation value is the Village in Kaipera at 953 V / M and the highest magnetic field effect value is at the Peak of Timingmang Hill which is 132.52 mT. Locations where exposure to ELF radiation waves were observed at all times, including those with high supernatural power backgrounds, according to the residents on Alor Island.